Liming of Acidic Soils with Belite Sludge - Aleksandr E. Isakov (Journal of Ecological Engineering, 2017)
The metallurgical enterprises are a major source of large-tonnage industrial wastes containing valued components. A significant discrepancy between the volumes of waste formations and its utilisation leads to the necessity of large-scale sludge dumping. The article describes a recycling method for belite sludge that is the waste of the alumina production from nepheline concentrate. The physical and chemical properties of belite sludge were analysed and the conclusions about the possibility and outlook of its using as an ameliorant were drown. The main results show that adding the belite sludge to acidic soils provides a certain positive effect. The main conclusions allow to say that belite sludges are an ecologically safe substance that can be used as a liming material for acidic soils.